Penilaian Tingkat Kematangan Proses Bisnis Pada Usaha Mikro, Kecil dan Menengah: (Studi Kasus) - Kurnia, Wahyu Ismail; Kisanjani, Alex; Kurnia, Rosna (Fakultas Teknik UMRI, 2023)
The readiness of Micro, Small, and Medium Enterprises (MSMEs) to achieve competitive advantage greatly depends on the maturity level of their business processes, which ultimately affects business performance. Therefore, this study aims to assess the level of business process maturity in MSMEs. The studied MSMEs are Salakilo and Bontings, both engaged in the culinary industry. These two MSMEs are classified as superior MSMEs according to the Borneo MSME Gate and Bank Indonesia in 2021. The assessment of business process maturity is conducted using the Business Process Orientation Maturity Model (BPOMM) with four levels and nine assessment aspects. Data collection is done through the distribution of validated questionnaires by experts and MSME practitioners. The questionnaire items are tailored to the specific conditions of the studied MSMEs, making it easier for the MSME practitioners to understand each assessment indicator. The results show that there is a difference in the level of business process maturity between Salakilo and Bontings MSMEs. Salakilo MSMEs have achieved the Integrated level with a score of 6.6, while Bontings MSMEs are at the Linked level with a score of 5.8. Keywords: Maturity Model, Business Process, MSME